Correlated response in body condition and energy mobilisation in rabbits selected for litter size variability - M.L. García (Animal, 2019)
A divergent selection experiment on litter size variability (high and low lines) was performed in rabbits over seven generations. The aim of this study was to evaluate the correlated responses to selection in body condition and fat reserves mobilisation. Litter size variability was estimated as phenotypic variance of litter size within female after correcting for the year-season and the parity-lactation status effects. A total of 226 females were used in this study, of which 158 females were used to measure body condition and energy mobilisation. Body condition was measured as BW and perirenal fat thickness. Females were stimulated with the adrenergic isoproterenol. Mobilisation capacity of fat reserves was measured by the lipolytic potential, defined as the increment in non-esterified fatty acids (NEFA) levels from basal concentration until adrenergic stimulation at mating, delivery and 10 days after delivery of the second reproductive cycle. Females were classified as survivor or non-survivor when they were culled for sanitary reasons or died before the third kindling. Data were analysed using Bayesian methodology. Survivor females presented higher BW than the non-survivor females at delivery (238 g, P=1.00) and 10 days after delivery (276 g, P=1.00). They also showed higher perirenal fat thickness at 10 days after delivery (0.62 mm, P=1.00). At delivery, basal NEFA levels was lower in survivor than non-survivor females (−0.18 mmol/l, P=1.00), but their lipolytic potential (∆NEFA) was higher (0.08 mmol/l, P=0.94). Body weight was similar between lines in survivor females. Perirenal fat thickness was lower in the high line than in the low line at delivery (−0.23 mm, P=0.90) and 10 days after delivery (−0.28 mm, P=0.92). The high line exhibited higher NEFA (0.10 mmol/l, P=0.93) and lower ∆NEFA (−0.08 mmol/l, P=0.92) than the low line at delivery. The low line showed a favourable correlated response to selection on body condition and fat reserves mobilisation. In conclusion, the low line selected for litter size variability seems to adapt better to adverse conditions, as it has a greater capacity to mobilise energy reserves at delivery than the high line. Females that adequately manage their body reserves and perform energy mobilisation correctly have a lower risk of dying or being culled.